IMPLEMENTASI METODE BRAINSTORMING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB KELAS VII DI MTS AL-IKHLAS NGIMBANG LAMONGAN - Shofiyani, Amrini; Afifah, Khanza (Universitas KH. A. Wahab Hasbullah, 2021)
This research was comducted with the aim of improving the Arabic speaking skills of seventh grade students at MTs Al-Ikhlas Lamongan by using the brainstorming method. This research was conductes from March to April 2021. The subjects of this study were all seventh grade students consisting of 10 female students and 10 male students. The form of research conducted by this research is research with the experimanl method, this method of application divides the class into 2 namely the experimental class and the control class. because of the lack of mastery of Arabic vocabulary, interest in learning Arabic, especially in speaking skills, is very minimal which makes the learning atmosphere in the classroom very quiet. Researchers try solutions by implementing the brainstorming method to MTs VII graders in improving Arabic speaking.